DUKUNGAN KELUARGA MEMPENGARUHI KEMAMPUAN ADAPTASI (PENERAPAN MODEL ADAPTASI ROY) PADA PASIEN KANKER DI YAYASAN KANKER INDONESIA CABANG JAWA TIMUR - R. Khairiyatul Afiyah (Jurnal Ilmiah Kesehatan, 2017)
Most patients with Cancer cannot adapt to their disease because they assume that it is a deadly disease. The purpose of this study was to find out the correlation between family support and adaptability of patients suffered from Cancer found at Yayasan Kanker Indonesia (Indonesian Cancer Foundation) located in East Java. This analytic study using cross sectional design involved the population of all people with Cancer found at Yayasan Kanker Indonesia located in East Java, totaling 30 patients. The samples of 27 patents were collected using simple random sampling technique. The independent variable was family support, whereas the dependent variable was adaptability. Questionnaires were used to collect the data analyzed using Mann-Whitney test with the level of significance α = 0.05. The result of study showed that most of the patients (70.4%) received good family support, whereas most of them (63.0%) had ability to adapt to their disease. Moreover, the result of Mann-Whitney test showed that p = 0.001 and the level of significance α = 0.05 so that H1 was accepted because p < 0.05. It showed that there was a correlation between family support and adaptability of patients suffered from Cancer found at Yayasan Kanker Indonesia located in East Java.The more family support, the more adaptive the patients with Cancer adapt to their disease. Hence, nurses are expected to give health education about the importance of family support to the family of patients with Cancer.